Overturn of Ilmenite‐Bearing Cumulates in a Rheologically Weak Lunar Mantle. Issue 2 (18th February 2019) - Yu, Shuoran; Tosi, Nicola; Schwinger, Sabrina; Maurice, Maxime; Breuer, Doris; Xiao, Long
Abstract: The crystallization of the lunar magma ocean (LMO) determines the initial structure of the solid Moon. Near the end of the LMO crystallization, ilmenite‐bearing cumulates (IBC) form beneath the plagioclase crust. Being denser than the underlying mantle, IBC are prone to overturn, a hypothesis that explains several aspects of the Moon's evolution. Yet the formation of stagnant lid due to the temperature dependence of viscosity can easily prevent IBC from sinking. To infer the rheological conditions allowing IBC to sink, we calculated the LMO crystallization sequence and performed high‐resolution numerical simulations of the overturn dynamics. We assumed a diffusion creep rheology and tested the effects of reference viscosity, activation energy, and compositional viscosity contrast between IBC and mantle. The overturn strongly depends on reference viscosity and activation energy and is facilitated by a low IBC viscosity. For a reference viscosity of 10 21  Pa s, characteristic of a dry rheology, IBC overturn cannot take place. For a reference viscosity of 10 20  Pa s, the overturn is possible if the activation energy is a factor of 2–3 lower than the values typically assumed for dry olivine. These low activation energies suggest a role for dislocation creep. For lower‐reference viscosities associated with the presence of water or trapped melt, more than 95% IBC can sink regardless of the activation energy. Scaling laws for Rayleigh‐Taylor instability confirmed these results but also showed the need of numerical simulations to accurately quantify the overturn dynamics. Whenever IBC sink, the overturn occurs via small‐scale diapirs. Plain Language Summary: The accretion of the debris resulting from the giant collision that formed the Earth‐Moon system caused the formation of a deep lunar magma ocean. The initial composition profile of the Moon results from the solidification of this magma ocean. One of the late solidification products is a thin layer containing ilmenite, which is highly enriched in titanium and forms over a depth of about 40–80 km. This layer is much denser than the underlying mantle, it tends thus to overturn and sink toward the core. The overturn hypothesis explains several features of the evolution of the Moon. However, the strong temperature dependence of the viscosity makes the part of the mantle where this titanium‐rich layer solidifies very stiff and its overturn very difficult. In this work, we used numerical simulations to infer which deformation properties the mantle needs to have for the overturn to be possible. We found that the overturn requires a significantly weaker and less temperature dependent viscosity than usually thought. The required low viscosity and its weak temperature dependence can be explained by the presence of water and residual melt in the Moon and/or by the effects of nonlinear deformation dependent both on temperature and stress. Key Points: We computed the crystallization sequence of the lunar magma ocean to simulate the overturn of ilmenite‐bearing cumulates Stagnant lid formation prevents the overturn unless the reference viscosity at 1600 K is 10 20 Pa s or lower Independent of the rheological parameters, ilmenite cumulates sink as small‐scale diapirs